Impact of earnings management on firm’s performance: A case study of manufacturing companies listed at the Dar-es-salaam stock exchange market - Moshi, Jane A (Mzumbe University, 2024)
A dissertation submitted in partial fulfillment of the requirements for the award of Master of Science in Accounting and Finance of Mzumbe University